2021
DOI: 10.3233/bmr-200195
|View full text |Cite
|
Sign up to set email alerts
|

The effect of brace treatment on pulmonary functions in adolescent idiopathic scoliosis: An 8-month follow-up study

Abstract: BACKGROUND: The instant effect of a brace on pulmonary functions of patients with adolescent idiopathic scoliosis (AIS) is known. However, the permanent effects of its regular use are still unclear. OBJECTIVE: This study aimed to determine whether a brace in patients with AIS had a permanent effect on respiratory functions. METHODS: Fifteen patients with a mean age of 13.2 ± 1.6 years, and a major Cobb angle of 25.8∘± 7.7∘ participated in this study. Lung volumes and respiratory muscle strength were measured w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Thus, exercise improves thoracic mobility. An 8-month follow-up investigation by Yasin et al [33] A review suggested that the three in uences of self-image, psychological well-being, and vitality should be considered to improve the quality of life of scoliosis patients under brace treatment when researching and designing new brace treatment regimens. The duration of brace wear is associated with the patient's initiative, but psychological factors and pain affect patient compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, exercise improves thoracic mobility. An 8-month follow-up investigation by Yasin et al [33] A review suggested that the three in uences of self-image, psychological well-being, and vitality should be considered to improve the quality of life of scoliosis patients under brace treatment when researching and designing new brace treatment regimens. The duration of brace wear is associated with the patient's initiative, but psychological factors and pain affect patient compliance.…”
Section: Discussionmentioning
confidence: 99%